Regulation of Dual Activity of Ascorbate Peroxidase 1 From Arabidopsis thaliana by Conformational Changes and Posttranslational Modifications - Kaur, Shubhpreet; Prakash, Prapti; Bak, Dong-Ho; Hong, Sung Hyun; Cho, Chuloh; Chung, Moon-Soo; Kim, Jin-Hong; Lee, Sungbeom; Bai, Hyoung-Woo; Lee, Sang Yeol; Chung, Byung Yeoup; Lee, Seung Sik (Frontiers in Plant Science, 2021)
Ascorbate peroxidase (APX) is an important reactive oxygen species (ROS)-scavenging enzyme, which catalyzes the removal of hydrogen peroxide (H2O2) to prevent oxidative damage. The peroxidase activity of APX is regulated by posttranslational modifications (PTMs), such as S-nitrosylation, tyrosine nitration, and S-sulfhydration. In addition, it has been recently reported that APX functions as a molecular chaperone, protecting rice against heat stress. In this study, we attempted to identify the various functions of APX in Arabidopsis and the effects of PTMs on these functions. Cytosol type APX1 from Arabidopsis thaliana (AtAPX1) exists in multimeric forms ranging from dimeric to high-molecular-weight (HMW) complexes. Similar to the rice APX2, AtAPX1 plays a dual role behaving both as a regular peroxidase and a chaperone molecule. The dual activity of AtAPX1 was strongly related to its structural status. The main dimeric form of the AtAPX1 protein showed the highest peroxidase activity, whereas the HMW form exhibited the highest chaperone activity. Moreover, in vivo studies indicated that the structure of AtAPX1 was regulated by heat and salt stresses, with both involved in the association and dissociation of complexes, respectively. Additionally, we investigated the effects of S-nitrosylation, S-sulfhydration, and tyrosine nitration on the protein structure and functions using gel analysis and enzymatic activity assays. S-nitrosylation and S-sulfhydration positively regulated the peroxidase activity, whereas tyrosine nitration had a negative impact. However, no effects were observed on the chaperone function and the oligomeric status of AtAPX1. Our results will facilitate the understanding of the role and regulation of APX under abiotic stress and posttranslational modifications.